Shariah compliance of green banking policy in Bangladesh. Issue 4 (14th November 2016) - Julia, Taslima; Rahman, Maya Puspa; Kassim, Salina
Abstract : Purpose: This paper aims to critically evaluate whether the policies of green banking set by Bangladesh Bank are Shariah compliant; according to the main sources of the Shariah – Quran and Sunnah. Design/methodology/approach: Green policy and guidelines have been divided into different categories such as environment protection, conservation of resources, risk management, educating people about green financing, transparency and disclosure and investing in green projects according to the common measures as stated in three different phases of the policy and guidelines. Subsequently, these major aspects of the green policy and guidelines are linked to the main references of the Shariah, i.e. the holy Quran and Sunnah of Prophet [peace be upon him (pbuh)]. Findings: Various verses of the holy Quran and teachings of Prophet (pbuh) related to the major categories of Green policy and guidelines are being presented to show the compliance with Shariah . Practical implications: The Green policy and guidelines are very much in-line with Shariah . Though all types of banks in Bangladesh are bound to implement the green banking policy, however, Shariah compliance of green banking policy will be encouraging for all Islamic Banks of Bangladesh for their further and profounder involvement in it. Social implications: As green policies are found to be Shariah complaint, the Islamic banks are expected to contribute more to the sustainable economic growth of the country by successfully implementing the green financing policies compare to their conventional counterpart. Originality/value: Verses of holy Quran and authentic Hadiths related to environmental sustainability concept show that Islam is a green religion as well as green banking policy is Islamic.